Cognitive Levels, Perceptions, and Attitudes of Pharmacists at Pharmacies toward Herbal Medicine - Diah Ari Purwaningsih; Yosef Wijoyo; Nunung Priyatni Waluyatiningsih (Sanata Dharma University, 2026)
Over the past decade, more than 50% of advanced countries and 80% of developing countries have used herbal medicines for primary care. Pharmacists provide strategic herbal medicine information, but their cognition, perceptions, and attitudes determine their effectiveness. This meta-analysis of studies from multiple countries examines pharmacists' cognition, perceptions, and attitudes toward herbal medicines. A qualitative meta-analysis was performed on seven cross-sectional studies from Indonesia, Malaysia, Spain, Saudi Arabia, and the US published between 2014 and 2024. Overall, 1,255 community pharmacists responded. Pharmacy cognition varied, with clinical effectiveness scoring highest (3.9/5) and mechanism of action scoring lowest (2.8/5). Only 36% of pharmacists routinely provided counseling, but 72% and 68% of pharmacists viewed herbal medicines as safe and effective. Service practices were influenced by cognitive level (r=0.68, p<0.05), practical experience (β=0.45), and continuing education training availability (OR=2.3, 95% CI: 1.8–2.9). This study shows that pharmacists need better education, ongoing training, side effect tracking systems, and collaboration with other professionals and the right policies to improve their skills. This will improve herbal medicine pharmaceutical services.